2022
DOI: 10.1186/s13048-022-00994-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis and artificial intelligence survival prediction of serous ovarian cancer based on preoperative circulating leukocytes

Abstract: Circulating leukocytes are an important part of the immune system. The aim of this work is to explore the role of preoperative circulating leukocytes in serous ovarian carcinoma and investigate whether they can be used to predict survival prognosis. Routine blood test results and clinical information of patients with serous ovarian carcinoma were retrospectively collected. And to predict survival according to the blood routine test result the decision tree method was applied to build a machine learning model.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Comparing these results with the logistic regression models data, AI revealed greater accuracy in 75% of analysis thanks to its ability to predict survival more or less than the median for each cohort outperforming logistic regression, confirming that AI is a better predictor of outcome than a traditional statistic system. A similar predicting survival AUC (.69) was described in the study of Feng et al 29 in which it is explored the role of preoperative circulating leukocytes in predicting survival prognosis of serous ovarian carcinoma. Another interesting finding of this paper is the relationship between the rising of monocytes and leucocytes and the worsening of prognosis, especially in terms of monocytes-to-leucocytes ratio: it confirms the fundamental importance of immune environment in EOC and this parameter should achieve more attention in AI algorithm.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Comparing these results with the logistic regression models data, AI revealed greater accuracy in 75% of analysis thanks to its ability to predict survival more or less than the median for each cohort outperforming logistic regression, confirming that AI is a better predictor of outcome than a traditional statistic system. A similar predicting survival AUC (.69) was described in the study of Feng et al 29 in which it is explored the role of preoperative circulating leukocytes in predicting survival prognosis of serous ovarian carcinoma. Another interesting finding of this paper is the relationship between the rising of monocytes and leucocytes and the worsening of prognosis, especially in terms of monocytes-to-leucocytes ratio: it confirms the fundamental importance of immune environment in EOC and this parameter should achieve more attention in AI algorithm.…”
Section: Discussionmentioning
confidence: 82%
“…Different AI methods were used in the single studies. In 4 out of 6 studies the authors declared to use one AI system to analyze data: Laios et al 25 applied k. NN (k-Nearest Neighbor), Laios et al 26 applied XGBoost Model (eXtreme Gradient Boosting Model), Bogani et al 27 applied ANN (Artificial Neural Network), Feng Y et al 29 applied MLDTA (Machine Learning Based Decision Tree Algorithm). Otherwise, multiple systems were used in Enshaei et al 24 and Laios et al 28 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the predictive potential of LMR in evaluating the prognosis of patients with various types of malignancies, including resectable ovarian cancer ( 8 , 9 , 27 29 ). In 2016, Eo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the predictive potential of LMR in evaluating the prognosis of patients with various types of malignancies, including resectable ovarian cancer (8,9,(27)(28)(29). In 2016, Eo et al first reported a correlation between low preoperative LMR and poor prognosis in ovarian cancer (9).…”
Section: Discussionmentioning
confidence: 99%